Cross-reactive, self-encoded polymer film arrays for sensor applications. Issue 86 (31st August 2016) - Fitzgerald, Jessica E.; Zhu, Jintao; Bravo-Vasquez, Juan Pablo; Fenniri, Hicham
Abstract : Simple and versatile spectroscopically-encoded styrene-based polymers are the basis for advanced e-Nose sensor array technology. Abstract : The development of chemical sensors continues to be an active area of research, especially for the development of a practical electronic nose. Here, we present a spectroscopic chemical sensor based on an array of 64 self-encoded polymer films deposited on a microfabricated silicon substrate. The polymer arrays were analyzed by FTIR and Raman spectroscopy before and after exposure to a series of organic volatiles to monitor changes in their vibrational fingerprints. We show here that the spectroscopic changes of self-encoded polymer films can be used to distinguish between volatile organic analytes. Changes induced in the sensor arrays by the analyte vapor were denoted by a spectroscopic response of the self-encoded polymer sensors and transformed into a response pattern by multivariate data analysis using partial least squares regression. The results indicated that the polymer sensors provide a unique and reproducible pattern for each analyte vapor and have the potential to be used in the fabrication of a novel electronic nose device.